2018
DOI: 10.3390/ijms19030899
|View full text |Cite
|
Sign up to set email alerts
|

Individual versus Combinatorial Effects of Silicon, Phosphate, and Iron Deficiency on the Growth of Lowland and Upland Rice Varieties

Abstract: Mineral nutrient homeostasis is essential for plant growth and development. Recent research has demonstrated that the occurrence of interactions among the mechanisms regulating the homeostasis of different nutrients in plants is a general rule rather than an exception. Therefore, it is important to understand how plants regulate the homeostasis of these elements and how multiple mineral nutrient signals are wired to influence plant growth. Silicon (Si) is not directly involved in plant metabolism but it is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…While deficit P supply decreased concentrations of different essential elements, such as K, Na, Ca, Mg, Fe, Mn, and Zn (Table 4), exogenous Si supply increased their concentration under low P conditions with a few exceptions. Among essential micronutrients, Fe is a key component of numerous proteins and enzymes and its deficiency impairs a number of metabolic processes in plants [19,20]. In cucumber, exogenous Si application alleviates Fe deficiency by regulating the expression of genes involved in Fe acquisition [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While deficit P supply decreased concentrations of different essential elements, such as K, Na, Ca, Mg, Fe, Mn, and Zn (Table 4), exogenous Si supply increased their concentration under low P conditions with a few exceptions. Among essential micronutrients, Fe is a key component of numerous proteins and enzymes and its deficiency impairs a number of metabolic processes in plants [19,20]. In cucumber, exogenous Si application alleviates Fe deficiency by regulating the expression of genes involved in Fe acquisition [20].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a large number of reports on the role of exogenous Si in relieving oxidative stress under abiotic stresses, such as drought, salinity, and high temperature, few reports have described the potential association between Si-induced amelioration of oxidative stress and improvement of macronutrient utilization efficiency [19]. In the present study, we showed that exogenous Si application not only alleviated LP-induced oxidative stress but also increased acquisition of most essential nutrients ( Figure 6), leading to potential improvement in nutrient utilization efficiency under low P supply.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that Pi deficiency leads to an increase of Fe content and alterations of other mineral elements [ 44 , 45 , 46 , 47 ]. In agreement with these reports, the contents of Fe were shown increased under Pi deficiency in the roots of both cultivars, particularly in the Scout 66, in which more than two fold-changes of Fe content were determined between Pi deficiency and Pi sufficiency.…”
Section: Resultsmentioning
confidence: 99%